1959
DOI: 10.1346/ccmn.1959.0080104
|View full text |Cite
|
Sign up to set email alerts
|

Further Correlations of Kaolinite Crystallinity with Chemical and Physical Properties

Abstract: Previous work has demonstrated that the degree of crystal perfection in kaolinite can be correlated with many physical properties. I n this paper some further relationships are shown, including surface area, base exchange capacity, total percentage of iron and titanium, and high-temperature mullitization. Surface area, base exchange capacity, and the total amount of iron and titanium in the clay increase as the degree of crystal perfection decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Numerous scholars have reported that crystal defects can increase the CEC of a mineral. For example, Murray and Lyons [32] stated that the differences in the CEC of various clay minerals have been attributed to differences in the degree of crystallinity. Ormsby et al [33] explored the exchange behavior of kaolines with various degrees of crystallinity and mentioned that the CEC was well correlated with the surface areas that were affected by changing from well crystallized to poorly crystallized kaolines.…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…Numerous scholars have reported that crystal defects can increase the CEC of a mineral. For example, Murray and Lyons [32] stated that the differences in the CEC of various clay minerals have been attributed to differences in the degree of crystallinity. Ormsby et al [33] explored the exchange behavior of kaolines with various degrees of crystallinity and mentioned that the CEC was well correlated with the surface areas that were affected by changing from well crystallized to poorly crystallized kaolines.…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…According to Murray and Lyons (1959), the rate of this transformation depends on the crystallinity of the primary kaolinite. Frost et al (2002) Drits et al (2016), and Percival et al (1974) summarized the diagnostic spectral absorption bands of the kaolinite-metakaolinite transition (Figure 1).…”
Section: Kaolinite-metakaolinite Transitionmentioning
confidence: 99%